Proposed new interior design scheme of Secret Garden Spa for The World Of Secret Garden Sdn Shd at 5.07, Level 2, Block D, Sunway Giza, No.2, Jalan Pju5/14, Pju5,Kota Damansara, 47810 Petaling Jaya, Selangor / Hanissa Mohd Nasir - Mohd Nasir, Hanissa (Faculty of Architecture, Planning and Surveying, 2011)
This final project entitled Proposed New Design Scheme of Secret Garden Spa for The World of Secret Garden Sdn. Bhd. is chosen. The reason this project is chosen is because the client, The World of Secret Garden Sdn. Bhd. already have plans to open up a few more branches in Malaysia upon it’s first spa located on the fourth (4th) floor of Puteri Pacific Hotel, Johor Baru, Johor. Alongside the Secret Garden personal care product range which has been in the market since 2006 makes it well-known amongst locals. Nowadays, many people are prefer to use a natural ingredient base product, which Secret Garden has to offer to it’s consumers. This project is first executed with wide-range of research which includes internet; archive of newspaper articles, the website of the Secret garden company, interview with client, and observation on site. The information collected is used as a guideline to execute this project. This proposed site of this project is located in the Klang Valley. This is because this type of service is becoming a trend or lifestyle among consumers to overcome hectic lifestyle and corporate stress. The objective of this design is to bring the image of Secret Garden Spa together with their services provided. It is also to bring up the sense of calmness arid revitalize consumers who come for their treatments